Alpha‐1‐antitrypsin deficiency (carrier) as possible risk factor for development of colonic diverticula. A multicentre prospective case–control study: the ALADDIN study. (1st September 2020) - Rottier, S. J.; Dreuning, L. C.; van Pelt, J.; van Geloven, A. A. W.; Beele, X. D. Y.; Huisman, P. M.; Deurholt, W. Y.; Rottier, C. A.; van Leeuwen, K.; de Boer, M.; van Mierlo, G.; Boermeester, M. A.; et al.
Abstract: Aim: Connective tissue changes due to ageing or diseases leading to changes in the colonic wall are one theory for the development of diverticula. Alpha‐1‐antitrypsin (A1AT), a protease inhibitor that protects connective tissue, possibly plays a role in the aetiology of diverticulosis. The aim of this study was to explore associations between the development of diverticula and A1AT deficiency. Methods: This was a multicentre prospective case–control study. A total of 221 patients aged ≥ 60 years with acute abdominal pain undergoing abdominal CT were included and analysed. Patients with diverticula were defined as the research group, patients without diverticula as controls. Genotype analysis for A1AT deficiency was performed. Results: Twenty‐six of 221 (11.8%) patients were diagnosed with (being a carrier of) A1AT deficiency. A non‐significant difference in prevalence between patients with and without diverticula was found, 20 (13.9%) of 144 vs 6 (7.8%) of 77, respectively, with a crude OR of 1.9 (95% CI 0.7–5.0; P  = 0.186) and after adjustment for confounders an adjusted OR of 1.5 (95% CI 0.5–4.0; P  = 0.466). A non‐significant difference in 30‐day mortality rate from acute diverticulitis between A1AT deficient patients (or carriers) and those without was observed: two (22.2%) of nine patients with A1AT deficiency vs 1 (1.8%) of 55 without. Conclusion: We found no convincing evidence that A1AT deficiency plays a role in the aetiology of diverticulitis, although deficient patients and carriers had a higher mortality when experiencing diverticulitis. Diverticulitis is a multifactorial disease and larger numbers may be needed to explore the role of A1AT deficiency among other contributing factors.